Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Toko Mebel Bu Kinto Wonogiri - Pramana, Bonggo Hastian Indra; , Drs. Ma'ruf, MM (2016)
This study aims to investigate the influence of service quality on customer satisfaction at Bu Kinto Furniture Store in Wonogiri. And to determine the variables that most influence on satisfaction in Bu Kinto Furniture Store in Wonogiri. The analysis tool used is multiple linear regression, to retrieve data using the method gives the consumer respondents to the questionnaire Furniture Store Bu Kinto in Wonogiri. This study refers to the positive approach, the approach which began the study with a hypothesis and then followed by hypothesis testing. From the analysis of each variable can be seen that variable tangiable, reliability, responsiveness, and assurance no significant effect on customer satisfaction at furniture stores Bu Kinto. And the results of the research shows that the variable empathy has the most powerful influence to variable customer satisfaction. It can be seen from the level of probability is the smallest compared to the variable tangiable, reliability, responsiveness, and assurance that is equal to 0.000.